Argentinean Bacillus thuringiensis strains exhibiting distinct morphology of their parasporal crystals - Peralta, Cecilia; Sauka, Diego Herman; Marozzi, Antonela Alejandra; del Valle, Eleodoro Eduardo; Palma, Leopoldo (Asociación Argentina de Microbiología, 2022)
Bacillus thuringiensis is a Gram-positive and sporulated bacterium exhibiting insecticidal activity against a wide range of insects.3 During sporulation, this bacterium produces a number of different proteins forming crystalline inclusions adjacent to the spores (parasporal crystals). Among these insecticidal proteins, the most abundant are those commonly known as Cry (Crystal) proteins, which are responsible for exerting a toxic activity (upon ingestion) against insects of different species.5 For this reason, B. thuringiensis has proved to be the most efficient and used bioinsecticide to date.2 However, Spodoptera cosmioides, Spodoptera eridania and Agrotis sp. (Lepidoptera) are species that are not yet controlled by some transgenic crops (e.g. Intacta RR2Pro soybean). Thus, in an attempt to enlarge the host spectrum of this bacterium it is necessary to search for novel strains. In this work we show a sporulated B. thuringiensis Bt-UNVM_84 strain exhibiting a number of rare amorphous to spherical crystal combinations, whereas sporulated B. thuringiensis strain Bt-UNVM-94 showed quasi symmetric bipyramidal parasporal crystals, by using scanning electron microscopy (SEM) (Fig. 1). Strains Bt-UNVM_84 and Bt-UNVM_94 were isolated from Oncativo (Córdoba, Argentina) and Cululú (Santa Fe, Argentina), respectively. The insecticidal activity of these different B. thuringiensis strains is currently under investigation. Each strain was grown in liquid CCY sporulation medium6 for ∼48h (150rpm) until no vegetative cells were observed under a light microscope. The presence of parasporal crystals was first determined using Coomassie blue stained slides1 (1000×) under a Nikon E100 light microscope and confirmed later by a Nikon Ti-Eclipse phase contrast microscope (1000×) (data not shown). For the SEM analysis, aliquots of 1ml were centrifuged for 5minutes (16,000g) at room temperature. Each pellet was washed three times with sterile distilled water and fixed with 100μl 4% formaldehyde. Each fixed preparation was then sent to Centro Integral de Microscopía Electrónica (CIME – CONICET – UNT) for SEM examination.